Índice topográfico de humedad para el diagnóstico de la amenaza por inundación en la subcuenca río Carrizal - Chang Zambrano, Martha Yamileth (2023)
The present investigation was carried out in the Carrizal river sub-basin in Calceta city, Manabí province, compiling elevation cartography, ranging from a maximum elevation of 544 meters to a minimum of 13 meters. The drainage network of the sub-basin exhibits a remarkable density of watercourses and drainage channels in the northwestern and eastern part. Some angles stand out, such as 2.1° (17.5% in 10,900 km²) and 8° (12% in 7,683 km²), which present the highest percentage of drainage directions in relation to the terrain topography. Terrain slopes were also considered, and it was found that 30% (18,754 km²) of the sub-basin area presents slopes of 15.2°. The topography is characterized by being moderate, combining relatively flat terrain with some gentle slopes. In terms of the Topographic Humidity Index (ITH), values of 7.3 were obtained, covering the greatest extension of the study area, occupying 43.62% (27,216 km²) of the territory. Followed by the humidity indexes 5.6, which cover 21% (13,702 km²), making it possible to establish that in the northern and northwestern region of the Carrizal river sub-basin there are areas of "High" and "Very High Flooding Regime", while the northeastern, eastern and southwestern areas present a "Low" and "Very Low Flooding Regime", demonstrating that the topographic humidity index influenced the categorization of the flood risk of the study area, so the following is accepted.